Factors Associated with Inadequate Birth Intervals in the BRISA Birth Cohort, Brazil - Raphael Barbosa; Maria Teresa Seabra Soares Britto Alves; Ian Nathasje; Deysianne Chagas; Vanda Ferreira Simões; Leonardo Silva (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective To determine the prevalence of inadequate birth interval and its associated factors in the BRISA study. Methods Cross-sectional study using data from the BRISA cohort. Birth interval was categorized into "adequate" (≥ 2 years or < 5 years between births), "short interval" (< 2 years) and "long interval" (≥ 5 years). The analysis of the factors associated with short and long birth intervals used multinomial logistic regression. Results The prevalence of adequate birth intervals was 48.3%, of long intervals, 34.6%, and of short intervals, 17.1%. Skin color, age, education level, economic status, type of delivery, number of prenatal visits, parity, blood pressure, diabetes, and anemia (p-value was < 0.2 in the univariate analysis) proceeded to the final model. The variable ≥ 3 births (odds ratio [OR] = 1.29; confidence interval [CI]: 1.01-1.65) was associated with short intervals. Age < 20 years old (OR = 0.48; CI: 0.02-0.12) or ≥ 35 years old (OR = 2.43; CI: 1.82-3.25), ≥ 6 prenatal visits (OR = 0.58; CI: 0.47-0.72), ≥ 3 births (OR = 0.59; CI: 0.49-0.73), and gestational diabetes (OR = 0.38; CI: 0.20-0.75) were associated with long intervals. Conclusion Older mothers were more likely to have long birth intervals, and higher parity increases the chances of short birth intervals. Furthermore, gestational diabetes and adequate prenatal care presented higher chances of having adequate birth intervals, indicating that health assistance during pregnancy is important to encourage an adequate interval between gestations.